A case of atypical prolonged hematologic toxicity with azacitidine in Chronic Myelomonocytic Leukemia (CMML), review of literature and a proposal of management - Elena Elli; Caterina Cecchetti; Angelo Belotti; Lorenza Borin; Enrico Maria Pogliani (Mediterranean Journal of Hematology and Infectious Diseases)
Hypomethylating drugs are useful and approved in the management of myelodysplastic syndromes (MDS) and Chronic Myelomonocytic Leukemia (CMML). However, phase 2 and 3 studies that assessed these agents in MDS, have included only a small number of CMML, and there are only few specific reports on CMML patients. Azacitidine is actually authorised for the treatment of CMML patients with 10-29% marrow blasts without myeloproliferative disorder who are not eligible for haematopoietic stem cell transplantation. This hypomethylating agent in MDS is known to cause transient cytopenias, most often occurring in the first 2 cycles. Here we report a case of atypical prolonged hematologic toxicity during azacitidine treatment in a CMML patient and we also review the literature regarding the efficacy of the drug and the management of hematologic adverse effects in specific CMML setting.